Inklusion und Gymnasium Studien zu Perspektiven von Lehrkräften und Studierenden - Rabenstein, Kerstin (Universitätsverlag Göttingen, 2020)
Inclusive teaching and school development is currently a central topic of educational research on schools, teaching, and professionalization. However, the German school type of Gymnasium (grammar school) is rarely taken into account. Nevertheless, changes in the general conditions and the associated reform expectations of the last decades are also reflected in studies on Gymnasium. With the three exploratory studies contained in this volume, we ask how inclusion at respectively for the Gymnasium is addressed by teachers at that type of school and by students in a Gymnasium teacher training program. The state of research on the perspectives of teachers as well as students in teacher training programs on inclusion is presented in a separate article. The discussion will be introduced with a contribution on the position of Gymnasium in the structured school system in Germany and the resulting challenges for an inclusive school development that includes the Gymnasium.